Delayed Puberty, Eroticism, and Sense of Smell, a Psychological Study of Economic and Social Consequences (Kallmann’s Syndrome): A Rare Case Report - Azlansyah Azlansyah; Cennikon Pakpahan; Hermansyah Hermansyah; Faisal Yusuf Ashari; Gustavo Santos Rainato; Kenley Nathanael; Maxwell Salvador Surya Atmaja (Biomolecular and Health Science Journal, 2024)
Kallmann syndrome is defined as the association of hypogonadotropic hypogonadism and anosmia or hyposmia caused by abnormal migration of olfactory axons and neurons producing gonadotropin-releasing hormone. It is a nonlife-threatening disease with relatively good treatment. However, the effects of the condition persist throughout the affected individuals’ lifetimes, leading to significant economic and social consequences. A man presented with eunuchoid body proportions complains about the size of his penis, absence of hair throughout the body, micropenis, and small testicles. Associated findings included hyposmia and a high-pitched voice. The patient experiences psychosexual impacts as a result of this illness. The patient could not undergo treatment to alleviate his genital size concern due to financial constraints as the treatment was not covered by government insurance.